La representación de nombres propios multipalabra en corpus analizados sintácticamente - Vincze, Orsolya (Acta Hispanica, 2011)
The present paper constitutes a first approach to the representation of multi-lexemic proper names insyntactically, annotated corpora. We provide a brief review of existing proposals on the description of thestructure of multi-lexemic proper names in linguistics, followed by a discussion of how these expressionsare treated in the field of Natural Language Processing, more specifically in annotated corpora. Finally,adopting the formalisms presented by the Meaning Ft>Text Theory, we propose a syntactic representationfor multi-lexemic proper names, concentrating on the semantic class of personal names in Galicianlanguage.